Distinguishing between HPV-Associated Metastatic Anal Squamous Cell Cancer and HPV-Associated Oropharyngeal Cancer - Steven Sorscher (Case Reports in Pathology)
The histology and immunohistochemistry (IHC) of primary and metastatic diseases from a human papilloma virus- (HPV-) related anal squamous carcinoma (ASCC) would typically demonstrate the same histology as an HPV-related oropharyngeal squamous carcinoma (OPSCC). However, determining whether a site of squamous cell carcinoma represents distant metastatic ASCC versus a metastatic HPV-related metastasis from an OPSCC to a regional lymph node carries profound prognostic and therapeutic implications. A patient with a history of locally advanced ASCC treated with standard concurrent radiation therapy and chemotherapy in 2015 is described. In 2018, an enlarged supraclavicular lymph node was excised demonstrating squamous cell carcinoma and radiographic staging revealed no other areas suspicious for malignancy. Direct laryngoscopy with operating telescope and biopsies demonstrated squamous cell carcinoma at the tongue base. Described here are assays that might be considered in distinguishing between whether a focus distant from a previously identified ASCC represents metastatic disease or instead a separate primary HPV-related cancer.